2020
DOI: 10.3390/catal10060612
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Reduction of Industrial and Municipal Wastewater by Advanced Oxidation Processes (Photo-Fenton, UVC/H2O2, Electro-Fenton and Galvanic Fenton): A Review

Abstract: The application of Fenton-based advanced oxidation processes (AOPs), such as photo-Fenton or electro-Fenton for wastewater treatment have been extensively studied in recent decades due to its high efficiency for the decomposition of persistent organic pollutants. Usually Fenton-based AOPs are used for the degradation of targeted pollutant or group of pollutants, which often leads to the formation of toxic by-products possessing a potential environmental risk. In this work, we have collected and reviewed recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…Residual H2O2 should be removed from treated wastewater before discharge or reuse. To avoid the presence of residual H2O2 in the treated water, two main approaches were implemented, namely the addition of relatively low concentrations of H2O2 (which can be completely consumed during the process) and filtration through activated carbon [38]. The addition of the catalyst MnTACN to H2O2/UV has no negative effect on Vibrio fischeri bacteria.…”
Section: Toxicity Test Resultsmentioning
confidence: 99%
“…Residual H2O2 should be removed from treated wastewater before discharge or reuse. To avoid the presence of residual H2O2 in the treated water, two main approaches were implemented, namely the addition of relatively low concentrations of H2O2 (which can be completely consumed during the process) and filtration through activated carbon [38]. The addition of the catalyst MnTACN to H2O2/UV has no negative effect on Vibrio fischeri bacteria.…”
Section: Toxicity Test Resultsmentioning
confidence: 99%
“…In the present study, the hybrid process of sono-electro-Fenton efficiently reduced the toxicity of the effluent after the decomposition of the cefixime under the optimal removal conditions. Results of studies conducted by other researchers have also shown the effective role of advanced oxidation processes in reducing the toxicity of pollutants using different species of organisms (24,25). In a study, Dirany et al evaluated the toxicity of sulfamethoxazole by bioassay using microorganisms and noted that the toxicity of the effluent treated with the electro-Fenton process was reduced by about 75%, compared to the inlet solution (26).…”
Section: Toxicity Resultsmentioning
confidence: 99%
“…1 Various types of wastewater. (Modified after [66]) (WWTP) outlets [17]. Additionally, a public study has raised public awareness that organic contaminants in wastewater, counting PPPCs, are existing in 80% of 139 US watercourses [35].…”
Section: Origin Of Pharmaceutical Wastewater (Pww)mentioning
confidence: 99%